Real-world study of patients with germline BRCA1/2-mutated human epidermal growth factor receptor 2‒Negative advanced breast cancer: Patient demographics, treatment patterns, adverse events, and physician-reported satisfaction in the United States, Europe, and Israel. (December 2022) - Mahtani, Reshma; Niyazov, Alexander; Arondekar, Bhakti; Lewis, Katie; Rider, Alex; Massey, Lucy; Lux, Michael Patrick
Abstract: Background: Current guidelines for the treatment of human epidermal growth factor receptor 2‒negative (HER2−) advanced breast cancer (ABC) are informed by tumor characteristics and include platinum- and non–platinum-based chemotherapy, chemotherapy plus immunotherapy, endocrine monotherapy, or endocrine therapy plus a targeted therapy. In addition, poly(adenosine diphosphate-ribose) polymerase inhibitors (PARPi) have recently demonstrated improved clinical and patient-reported outcomes and manageable toxicity profiles compared with chemotherapy in patients with germline breast cancer susceptibility gene 1 or 2 (g BRCA1/ 2)‒mutated HER2− ABC in clinical trials and are now approved to treat this patient population. This study provides complementary real-world data regarding treatment patterns, adverse events, and physician-reported treatment satisfaction in this population. Methods: This retrospective analysis using the Adelphi Real World ABC Disease Specific Programme in the United States, European Union, and Israel included patients aged ≥18 years receiving therapy for stage IIIb or IV g BRCA1/ 2-mutated HER2− ABC. Oncologists completed a patient record form detailing patient demographics, clinical assessments, and treatment history and a survey regarding their use of and satisfaction with treatments. Results: Among the 543 patients, mean age was 55 years, 25% were premenopausal, 70% had hormone receptor‒positive (HR+) ABC, and 30% had triple-negative breast cancer (TNBC). PARPi were used in 5%, 11%, and 12% of first-line, second-line, and third-line therapies, respectively, for patients with HR+ ABC; for TNBC, percentages were 18%, 44%, and 36%. Across treatment lines, neutropenia, anemia, and nausea occurred in 16%, 24%, and 32% of patients receiving PARPi, respectively; 22%, 38%, and 33% of patients receiving platinum chemotherapy; and 20%, 20%, and 33% of patients receiving non–platinum-based chemotherapy. Physician satisfaction was highest with PARPi and with chemotherapy plus immunotherapy. Conclusions: Findings in this real-world population complement clinical trial observations and provide further support for treatment of patients with PARPi in g BRCA1/2 -mutated HER2− ABC. Highlights: Treatments were evaluated in germline BRCA1/2 -mutated HER2− breast cancer patients. Physician-reported treatment patterns demonstrated PARPi use in this population. Nausea and anemia were the most common adverse events in those receiving PARPi. Physician satisfaction was highest with PARPi and chemotherapy plus immunotherapy. These real-world findings lend further support for PARPi use in this population.